2019
DOI: 10.1158/1078-0432.ccr-19-0173
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Microenvironment in Hormone Receptor–Positive Breast Cancer Before and After Preoperative Chemotherapy

Abstract: Purpose: Hormone receptor-positive/HER2-negative (HR þ /HER2 À ) breast cancer is associated with low levels of stromal tumor-infiltrating lymphocytes (sTIL) and PD-L1, and demonstrates poor responses to checkpoint inhibitor therapy. Evaluating the effect of standard chemotherapy on the immune microenvironment may suggest new opportunities for immunotherapy-based approaches to treating HR þ /HER2 À breast tumors.Experimental Design: HR þ /HER2 À breast tumors were analyzed before and after neoadjuvant chemothe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 43 publications
5
77
0
Order By: Relevance
“…Additional non-radiation based treatment might be appropriate, as there is evidence of macrophage induced radio-resistance after TAM cancer cell fusion [35,36]. Waks et al also reported a possible role for M2-like macrophages in chemo-resistance in HR+ breast cancer [37]. These results demonstrate that macrophage polarisation targeting therapies like CSF inhibitors might become valuable therapeutic options for breast cancer treatment [38,39].…”
Section: Discussionmentioning
confidence: 91%
“…Additional non-radiation based treatment might be appropriate, as there is evidence of macrophage induced radio-resistance after TAM cancer cell fusion [35,36]. Waks et al also reported a possible role for M2-like macrophages in chemo-resistance in HR+ breast cancer [37]. These results demonstrate that macrophage polarisation targeting therapies like CSF inhibitors might become valuable therapeutic options for breast cancer treatment [38,39].…”
Section: Discussionmentioning
confidence: 91%
“…Some study reported that the presence of intratumoral CD8 + lymphocytes was not associated with breast cancer-speci c survival in ER + breast tumors (7). Another study found that higher levels of CD8 + T cells were associated with favorable responses to neoadjuvant chemotherapy, but not with improved outcomes (15). In contrast, two studies revealed that LBC regardless of the HER2 status with high CD8 + T-cells in ltration were associated with unfavorable outcome (16,26), which are contrary to our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the potential clinical relevance of TILs in LBC have generated mixed results. Some studies reportied that TILs or CD8 + T-cells had no prognostic value in LBC (1,7), whereas two studies reported that high TILs conferred a signi cantly higher likelihood of pCR in LBC patients, although they did not signi cantly improve long-term outcomes (14,15). Similarly, another study showed that a high CD8 + T-cell exhaustion signature score, indicating a low CD8 + T-cell level, was associated with worse disease-free survival (DFS) in LBC patients regardless of HER2 status (16).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells often express programmed cell death-ligand 1 (PD-L1) and subsequently induce T-cell apoptosis, and PD-L1 status is an important factor in the prediction of the clinical outcome following RT in BRCA patients [22]. However, a comprehensive analysis of the correlation of RT outcome with immune infiltration has not yet been reported [23].…”
Section: Introductionmentioning
confidence: 99%